The Analysis of Uncertainty Resolution in Capital Budgeting for new Products - Van Horne, James C. (Management Science, 1969)
In this paper, a method is developed for analyzing the resolution of uncertainty over time for the individual new product and for combinations of existing and new products, or the firm's over-all product mix. Probability concepts are employed, and it is shown that new products can be evaluated according to their marginal impact upon the resolution of the uncertainty pattern for the firm's total product mix. The analysis of this dimension is undertaken within a capital-budgeting framework, allowing a GO or NO decision to be reached for the new product under consideration. Information about when uncertainty is expected to be resolved enables management to evaluate more realistically the effect of a new-product decision on the riskiness of the firm's entire product mix. This knowledge is valuable in planning for new products and in balancing the firm's risk over time. As a result, more rational capital budgeting for new products is possible.